An empirical comparison of sustainable and responsible investment ṣukūk, social impact bonds and conventional bonds - Syed Marwan Mujahid Syed Azman; Suhaiza Ismail; Mohamed Aslam Haneef; Engku Rabiah Adawiah Engku Ali (ISRA International Journal of Islamic Finance, 2022)
Purpose - The objectives of this paper are two-fold: first, to empirically compare and contrast the salient features of three financial instruments (FIs), namely sustainable and responsible investment (SRI) ṣukūk, social impact bonds (SIBs) and conventional bonds (CBs) and second, to examine the differences between the perceptions of the investors and the developers on the features of the three FIs. Design/methodology/approach - Using a questionnaire survey, 251 completed and useable responses were received, representing a 42.54% response rate. In examining the differences and similarities in the characteristics of the three FIs, the inferential statistical of frequency and percentage were used. Wilcoxon and Mann-Whitney tests were conducted to investigate the differences in the salient features of the three FIs and the differences between the investors and developers' perceptions on the salient features of SRI ṣukūk, SIBs and CBs, respectively. Findings - The results reveal that stakeholders view SRI ṣukūk, SIBs and CBs to be statistically significantly different from each other. This shows that stakeholders do not view SRI ṣukūk as "old wine in a new Sharīʿah-compliant bottle" but instead considered different from SIBs and CBs. Furthermore, stakeholders also differentiate between SIBs and CBs. Originality/value - The paper provides empirical evidence that Islamic finance (IF) instrument, represented by SRI ṣukūk, is viewed as different instruments to conventional tools, represented by SIBs and CBs. First, it debunks the notion that IF is viewed as similar to its conventional counterpart. Second, SIBs are seen as different from CBs, illustrating the distinct categorisation of impact investing instruments. As such, third, the development of SRI ṣukūk and SIBs can provide diversification to portfolios as it is a unique instrument in the social finance and financial market.
Keywords: 330; Conventional bonds; Islamic finance; Social impact bonds; SRI ṣukūk